Antimicrobial Susceptibility Pattern of Escherichia coli Isolated from Uninary Tract Infected Patients Attending Bir Hospital - Sharma, Amit Raj; Bhatta, Dwij Raj; Shrestha, Jyotsna; Banjara, Megha Raj (Nepal Journal of Science and Technology, 2013)
Correction: on 23/08/2014, the spelling of 'Uninary' in the title was changed to 'Urinary'. Antibiotic resistance among uropathogens is emerging public health problem. This study was done for assessing antibiotic and multidrug resistance (MDR) patterns of Escherichia coli at Bir Hospital, Kathmandu, among suspected urinary tract infection (UTI) patients from January to March, 2011. Altogether, 739 urine samples were analysed by semi-quantitative culture method and uropathogens were identified by conventional methods. E. coli was tested (109 samples) for antimicrobial susceptibility by Kirby Bauer disc diffusion method as per Clinical and Laboratory Standard Institute (CLSI) guidelines. Out of 739 samples, 27.3% gave significant growth of E. coli while 3.1% and 29.2% samples gave mixed and non-significant growth respectively. E. coli was found to be most predominant isolate (54.0%) followed by coagulase negative Staphylococci (CoNS) (21.3%) and Enterococcus spp. (7.3%). Nitrofurantoin was found to be the most effective antibiotic followed by ciprofloxacin and ofloxacin while cephalexin was least effective. Out of 109 E. coli isolates, 90.8% were MDR strains and most of the isolates had a very high multiple antibiotic resistance (MAR) index, suggesting the origin of the isolates to be of high antibiotic usage. E. coli showed higher rate of resistance towards commonly used oral antibiotics. However, nitrofurantoin is still active against organisms. Thus, nitrofurantoin could be the choice for empirical therapy of UTI. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 177-184 DOI: http://dx.doi.org/10.3126/njst.v14i1.8938